Impact of Social Media on the Buying Choices of Shoppers - Agarwal, Varsha (International Journal For Multidisciplinary Research, 2022)
Using social media is an integral part of our lives. It is a great way to connect the world and keep people informed about new happenings around them. Social media has also become a space for people to truly express themselves and make a positive impact on this planet. However, excess use of social media has made it a parasite growing on peoples’ empty minds. The audiences of social media apps are highly influenced by the content they see on them. Social media is said to influence buyer behaviour significantly. Consumer buying behaviour is a combination of customer’s attitudes, intentions, preferences and decisions while purchasing a product or service. Purchases are considered risky and therefore decision-making processes are information intensive. Growth in Social media marketing over the last 10 years is because of the increasing fame of social media sites such as Twitter and Instagram which promote the habit of living life in quick succession by connecting people through stories and reels, tweets and pictures. The main purpose of this investigation is examining the impact of social media on buying choices of the customers. This investigation was carried by conducting a survey, and by taking interviews. The survey also focuses on understanding the impact of influencers on the audience.
ISME
Keywords: Social Media; Consumer Behaviour; Marketing; Digital Marketing; Buyer Behaviour; Customer; Decision Making